Compensatory enhancement of orexinergic system functionality induced by amyloid-β protein: a neuroprotective response in Alzheimer’s disease - Zhuang, Chenyu; Yan, Hengyu; Lu, Jiayu; Zhou, Yifan; Liu, Yanqing; Shi, Guoshan; Li, Yan (Frontiers in Physiology, 2025)
BackgroundAmyloid-β protein (Aβ) accumulation is a defining characteristic of Alzheimer’s disease (AD), resulting in neurodegeneration and a decline in cognitive function. Given orexin’s well-documented role in enhancing memory and cognition, this study investigates its potential to regulate Aβ-induced neurotoxicity, offering new perspectives into AD management.MethodsThis paper simulated Aβ accumulation in the hippocampus of AD patients by administering Aβ1-42 oligomers into the bilateral hippocampal dentate gyrus of ICR mice. Inflammatory cytokines (IL-6, TNF-α) and orexin-A levels were measured by ELISA. Additionally, the excitability of orexinergic neurons was assessed by IHC targeting c-Fos expression. These methodologies evaluated the Aβ-induced neuroinflammation, orexinergic system functionality, and dexamethasone’s (Dex) effects on these processes.ResultsInjection of Aβ1-42 oligomer resulted in elevated levels of IL-6, TNF-α, and orexin-A in the hippocampus, as well as increased excitability of orexinergic neurons in the lateral hypothalamus (LH). Dex treatment reduced neuroinflammation, causing a reduction in orexin-A levels and the excitability of orexinergic neurons.ConclusionAβ-induced neuroinflammation is accompanied by enhanced levels of orexin-A and orexinergic neuron excitability. These findings suggest that the enhanced functionality of the orexinergic system may become a compensatory neuroprotective mechanism to counteract neuroinflammation and enhance cognitive function.